METHOD OF LABORATORY ANALYSIS FOR OIL SHALE ASSAY - Herlan Adim (Testing Center for Oil and Gas LEMIGAS, 2004)
Oil shale is much commoner than is generally realized, occuring on every continent and in every geological system. They are misnamed, but it is unlikely that any more appropriate name will be acceptable either to geologists. Few important deposits actually consist of shales and even fewer have yielded any oil. In the conventional sense most